2015
DOI: 10.1155/2015/104812
|View full text |Cite
|
Sign up to set email alerts
|

Oral Lesions Induced by Chronic Khat Use Consist Essentially of Thickened Hyperkeratinized Epithelium

Abstract: Objectives. The habit of khat chewing is prevalent in many Middle Eastern and African cultures and has been associated with various adverse conditions in humans. This study aimed to describe histological changes induced by chronic khat chewing on the buccal mucosa. Methods. Biopsies of the buccal mucosa from 14 chronic khat chewers, 20 chronic khat chewers who also smoked tobacco, and 8 nonchewers were compared for epithelial thickness, degree and type of keratinization, and connective tissue changes. Results.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 21 publications
(32 reference statements)
1
20
0
Order By: Relevance
“…Mucosal pigmentation related to khat chewing has also been reported in the literature . Yarom et al .…”
Section: Oral Manifestations Of Khat Usagementioning
confidence: 76%
See 4 more Smart Citations
“…Mucosal pigmentation related to khat chewing has also been reported in the literature . Yarom et al .…”
Section: Oral Manifestations Of Khat Usagementioning
confidence: 76%
“…attributed mucosal discoloration to the chemical components of khat. A recent study observed a high concentration of melanin in basal keratinocytes of tissue samples of chronic khat chewers, which could explain the mucosal discoloration at the khat chewing site …”
Section: Oral Manifestations Of Khat Usagementioning
confidence: 98%
See 3 more Smart Citations